The Effect of Using Animation Video on the Eight Grade Students’ Vocabulary Achievement at SMPN 5 Jember - Ahsin Fahmi Mubarok; Siti Sundari; Eka Wahjuningsih (FKIP e-PROCEEDING, 2017)
Abstract: Vocabulary which plays an important role in mastering all English skills must be taken into account so that students are able to master all language skills properly. Animation video is regarded as the appropriate teaching media to facilitate the students to enhance their vocabulary achievement since it stimulates students’ autonomy and proactivity and motivates students’ passion for learning English. Besides, it portraits the realistic situations in life and provides the students with direct access to learn the culture of English. This research was intended to know whether or not there is a significant effect of using animation video on students’ vocabulary achievement at SMPN 5 Jember in the 2016/2017 academic year. The respondents were VIII-A (experimental class) and VIII-B (control class) that were determined after analyzing the result of homogeneity test which showed that the population was homogeneous. The output of independent sample t-test by using SPSS showed that the value of sig column in the first row was 0.000 and this value was less than 0.05 (p < 0.05). Consequently, the alternative hypothesis: “There is a significant effect of using animation video on the eighth grade students’ vocabulary achievement at SMPN 5 Jember” was accepted. Considering the results of the vocabulary test, it was concluded that the use of animation video had a significant effect on the eighth grade students’ vocabulary achievement at SMPN 5 Jember in the 2016/2017 academic year. As a result, animation video is strongly suggested to be used as an effective media to teach vocabulary. Key words: Teaching media, animation video, vocabulary achievement